Bile duct carcinoma recurrence in the papillary region in a long-term survivor of hilar cholangiocarcinoma: a case report. (December 2016) - Buchner, D.; Drebber, U.; Chang, D.; Stippel, D.
Abstract Background Because of its high rate of early recurrence and its poor prognosis, long-term survival after cholangiocarcinoma is rare; therefore, only limited information on patients surviving more than 5 years after surgical therapy is available. Case presentation We report the case of a 57-year-old white man who developed a distal bile duct carcinoma 9 years after curative surgical therapy of intrahepatic cholangiocarcinoma. He had undergone a right lobe hemihepatectomy 11 years ago. Nine years later, he was diagnosed with a distal bile duct carcinoma and a duodenopancreatectomy was performed. On histologic examination both carcinomas revealed a tubular and papillary growth pattern with cancer-free resection margins and for both carcinomas there were no signs of lymphatic infiltration or metastatic spreading. Targeted next-generation sequencing showed an identical activating mutation pattern in both carcinomas. Conclusions Late recurrence of cholangiocarcinoma, even anatomically distant to the primary, in long-time survivors is possible and could be caused by a distinct tumor biology. A better understanding of the individual tumor biology could help hepatologists as well as hepatobiliary and pancreatic surgeons in their daily treatment of these patients.